Nutritional assessment in idiopathic pulmonary fibrosis: a prospective multicentre study. Issue 1 (7th March 2022) - Faverio, Paola; Fumagalli, Alessia; Conti, Sara; Madotto, Fabiana; Bini, Francesco; Harari, Sergio; Mondoni, Michele; Oggionni, Tiberio; Barisione, Emanuela; Ceruti, Paolo; Papetti, Maria Chiara; Bodini, Bruno Dino; et al.
Background: Nutritional status impacts quality of life and prognosis of patients with respiratory diseases, including idiopathic pulmonary fibrosis (IPF). However, there is a lack of studies performing an extensive nutritional assessment of IPF patients. This study aimed to investigate the nutritional status and to identify nutritional phenotypes in a cohort of IPF patients at diagnosis. Methods: Patients underwent a thorough pulmonary and nutritional evaluation including questionnaires on nutritional status, and physical activity, anthropometry, body impedance, dynamometry, 4-m gait speed and blood tests. Results: 90 IPF patients (78.9% males, mean age 72.7 years) were enrolled. The majority of patients were classified as Gender-Age-Physiology Index stage 2 (47, 52.2%) with an inactive lifestyle according to International Physical Activity Questionnaire score (39, 43.3%), and had mean forced vital capacity and diffusing capacity for carbon monoxide 86.5% and 54.2%, respectively. In regards to nutritional phenotypes, the majority of patients were normally nourished (67.8%, 95% CI 58.6–77.7%), followed by non-sarcopenic obese (25.3%, 95% CI 16.1–35.2%), sarcopenic (4.6%, 95% CI 0.0–14.5%) and sarcopenic obese (2.3%, 95% CI 0.0–12.2%). Among the normally nourished, 49.2% showed early signs of nutritional and physical performance alterations, including body mass index ≥30 kg·m −2 in 4.3%, history of weight loss ≥5% in 11.9%, and reduction of gait speed and hand grip strength in 11.9% and 35.6%, respectively. Low vitamin D values were observed in 56.3% of cases. Conclusions: IPF patients at diagnosis are mainly normally nourished and obese, but early signs of nutritional and physical performance impairment can already be identified at this stage. Patients with IPF at diagnosis are mainly normally nourished and obese but early signs of nutritional and physical performance impairment can already be identified. Sarcopenia is identified only in a minority of cases; cachexia has not been observed. https://bit.ly/3kZuRh2